Post-quantum cryptography - Bernstein, Daniel J. (Springer, 2017)
Quantum computers may break popular public-key cryptographic systems, including RSA, DSA, and ECDSA. This book introduces the reader to the next generation of cryptographic algorithms, the systems that resist quantum-computer attacks: in particular, post-quantum public-key encryption systems and post-quantum public-key signature systems.